Modulation of chemokine production and expression of adhesion molecules in renal tubular epithelial and endothelial cells by catecholamines - Kapper, Silke; Beck, Grietje; Riedel, Saskia; Prem, Katharina; Haak, Markus; Woude, Fokko J. van der; Yard, Benito A. (Transplantation, 2002)
BACKGROUND: The present study was conducted to investigate whether catecholamines influence the production of chemokines and adhesion molecules in proximal tubular epithelial cells (PTECs) and endothelial cells. METHODS: PTECs and human umbilical vein endothelial cells (HUVECs) were stimulated with various concentrations of dopamine (DA), adrenaline (AD), or noradrenaline (NA), and the production of interleukin (IL)-8, ENA-78, and Gro-alpha was assessed by ELISA. The influence of catecholamine pretreatment on tumor necrosis factor (TNF)-alpha-mediated production of these chemokines and the expression of adhesion molecules was also tested. RESULTS: In PTECs, DA inhibited the production of all three chemokines in a dose-dependent fashion. Although inhibition in ENA-78 and Gro-alpha production was also found in HUVECs, IL-8 production was up-regulated in these cells. Increased IL-8 secretion was predominantly observed at the apical site of the cells. In AD or NA stimulated cells, the production of Gro-alpha was increased in PTECs and decreased in HUVECs. Down-regulation in IL-8 production was also observed after AD but not after NA stimulation of both cell types. Interestingly, TNF-alpha-mediated up-regulation in intercellular adhesion molecule 1, vascular cell adhesion molecule (VCAM), and E-selectin was delayed in DA-pretreated HUVECs but not in PTECs. The influence of DA, but not AD or NA, on chemokine production was completely prevented by the addition of N-acetylcysteine. CONCLUSIONS: This study demonstrates that catecholamines differentially influence chemokine production and indicates that DA may have anti-inflammatory properties because it delays the expression of adhesion molecules and inhibits the production of chemokines in PTECs and endothelial cells under basal and inflammatory conditions.
Gesehen am 29.06.2022